Association of anxiety and depression with cognitive challenges in children in Bangladesh - M. Iftakhar Alam; Mohaimen Mansur (PLoS ONE, 2026)
This study primarily investigated the association of anxiety or depression (AD) with communication, learning, remembering, or concentrating (CLRC) difficulties in children aged 5-17 years in Bangladesh. Data were taken from the 2019 Bangladesh Multiple Indicator Cluster Survey (MICS). Random intercept binary logistic regression model was used to assess the association between CLRC and AD, after controlling sex, age, division, maternal education, maternal functional difficulty, and wealth index. Children with AD difficulties had significantly higher odds of CLRC (OR = 7.82; 95% CI: 6.29–9.73). Males were 30% more likely to have CLRC than females (OR = 1.30; 95% CI: 1.12–1.51). Compared with children living in Barishal-the reference administrative region-children residing in several other divisions had significantly lower odds of experiencing CLRC. Children of mothers with secondary education had reduced odds of CLRC (OR = 0.80), while those whose mothers had functional difficulties had higher odds (OR = 3.00). To conclude, AD difficulties is strongly associated with CLRC, alongside other factors like sex, geographic location, maternal education, and wealth. Addressing these factors is crucial for reducing CLRC difficulties in children.